SEISMIC HAZARD MAP FOR JAVA ISLAND BY 3D SOURCE MODEL WITH HAZUS SOFTWARE (USGS) - RUDOLPH P. N. , FRITZ
Indonesia is a country that was very vulnerable to the earthquake hazard. Earthquakes with large magnitude very often occur in this region. Seismic hazard analysis should be done to map the earthquake zonation for Indonesia. National building code for seismic design that commonly practice was the SNI-1726-2002, including seismic hazard map of Indonesia region. This map is reproduce based on the average result of some researcher with different in source model. Seismic hazard analysis with 3D source model will give a reasonable result compare to that 2D source model analysis. In this thesis we use 3D source modeling with the help of hazUS software developed by the USGS (United States Geological Survey). This HazUS software was a freeware, which in the mid of 2007 a Tim from USGS came to Indonesia and made a training of how to use HazUS to compute seismic hazard analysis. Some benefit using this software were in fact that this program use 3D source modeling and embedded newest attenuation function NGA (Next Generation Attenuation) while the user interface still need improvement. Total probabilities theorem (McGuire, 1976) adopted in the calculation of seismic hazard analysis in HazUS. This software could also calculate the single-site hazard, in this thesis hazard at Jakarta site was chosen to be determined. Hazard curves, spectral responses for Jakarta with 475 and 2475 years return period was offered. Generally, spectral acceleration at Jakarta site with 3D source modeling was larger than the SNI-1726-2002.